2016
DOI: 10.1149/2.0281606jss
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Blue InGaN Light-Emitting Diodes with P-GaN/InGaN SPS Last Barrier and P-AlGaN/GaN SPS EBL

Abstract: The numerical simulations of blue InGaN/GaN light-emitting diodes (LEDs) with the combined structures of p-GaN/InGaN shortperiod superlattice (SPS) last barrier (LB) and p-AlGaN/GaN SPS electron blocking layer (EBL) are investigated by the Advance Physical Model of Semiconductor Devices (APSYS) program. The simulation results show that the newly designed LEDs get better performances over the original structure of InGaN/GaN LEDs. This is attributed to the enhancement of the hole injection efficiency and the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] However, based on the remarkable difference in refractive index between the surrounding air (n = 1) and GaN (n = 2.5), the critical angle of total internal reflection (TIR) is only of 23.5°, which seriously suppresses the total light output attributed to the lower light extraction efficiency (LEE) and the lower external quantum efficiency (EQE) of GaN/InGaN LEDs. [10][11][12][13] Recently, various methods, e.g., pattern sapphire substrate, 14 backside reflector, 15 antireflection layer, 16 textured surfaces and sidewalls, 17,18 microhole array, 19 photonic crystal structure, 20 and hybrid surface structure 21 have been reported to upgrade the performance of GaN/InGaN LEDs. Moreover, the current spreading (CS) is an important issue for GaN/InGaN LEDs.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] However, based on the remarkable difference in refractive index between the surrounding air (n = 1) and GaN (n = 2.5), the critical angle of total internal reflection (TIR) is only of 23.5°, which seriously suppresses the total light output attributed to the lower light extraction efficiency (LEE) and the lower external quantum efficiency (EQE) of GaN/InGaN LEDs. [10][11][12][13] Recently, various methods, e.g., pattern sapphire substrate, 14 backside reflector, 15 antireflection layer, 16 textured surfaces and sidewalls, 17,18 microhole array, 19 photonic crystal structure, 20 and hybrid surface structure 21 have been reported to upgrade the performance of GaN/InGaN LEDs. Moreover, the current spreading (CS) is an important issue for GaN/InGaN LEDs.…”
mentioning
confidence: 99%
“…Regarding the mechanisms of efficiency droop, the main physical explanations have been investigated and proposed such as: carrier delocalization, [1][2][3][4] Auger recombination, [5][6][7][8] junction heating, 9,10 current spreading, 11,12 electron overflow, [13][14][15][16] and poor hole injection. [17][18][19][20] However, the origin of the efficiency droop mechanism for GaN-based LEDs is still a controversial and uncertain issue until now. Yang et al reported that the current dependence of both the quantum efficiency and peak shift appeared to be a strong function of the indium content in the active region.…”
mentioning
confidence: 99%